Implementation of Augmented Reality to Improve Students' Understanding of Science Concepts in Elementary Madrasahs - Rika Widyaningsih; Sri Yulia Sari; Heroza Firdaus (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to determine the application of Augmented Reality (AR) technology in science learning and the improvement of conceptual understanding among fifth-grade students at Al-Munawwarah Islamic Elementary School in Jambi City after using this media. The study used the Classroom Action Research (CAR) method with the Kemmis & MC Taggart model, implemented in two cycles, each consisting of planning, action, observation, and reflection. The results showed that the use of Augmented Reality media was able to gradually improve students' conceptual understanding, as evidenced by the percentage of learning completion, which increased from 64% in the pre-cycle, 68% in the first meeting of Cycle I, 72% in the second meeting of Cycle I, 76% in the first meeting of Cycle II, and reached 88% in the second meeting of Cycle II, categorized as very good. Thus, the application of Augmented Reality media has proven effective in helping students understand abstract science concepts and increasing their learning engagement and motivation.